Mechanization and Adaptation: Empowering Human Resources in the Era of Automation - kumar Rathod, Vinod (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
Given the significant advancements made in artificial intelligence, machine learning, and other technologies, the emergence of machines appears inevitable. Abstract The findings of this study counsel corporate executives to welcome change and devise strategies for reaping its benefits. Everything in the world will be automated by robots, which are here to stay. As technology develops quickly, HR will need to advance to keep up, which will eventually lead to the complete automation of HR functions. Human resources won’t be an exception to this trend; the nature of work in the future will be more interdisciplinary, technologically advanced, multichannel, and cross-functional. The results of the study survey show that intelligent robotic systems offer a novel method for managing employees and enhancing business performance. There are many opportunities in the subject of human resources (HR), as well as several inherently problematic technological and ethical problems. Robotic automation has implications for HR strategies like work substitution, collaboration between humans and machines, visionary decision-making, and learning experiences. It also has implications for HR activities like recruitment, training, and development, conflict resolution, organisational discipline, culture, and work performance. The HR function will need to alter significantly and actively embrace robotic technology if it wants to be relevant.